Validation of Antiobesity Effects of Black Soybean Seed Coat Powder Suitable as a Food Material: Comparisons with Conventional Yellow Soybean Seed Coat Powder - Moriyasu, Yuuki (Foods, 2021)
In this study, we fed obese model mice black soybean seed coat powder (BSCP) and evaluated the antiobesity effects. As a control, normal yellow soybean seed coat powder (YSCP) was used. C57BL/6J, a high-fat diet-induced obesity model mouse, was fed a high-fat diet containing BSCP or YSCP (20% fat) to induce obesity. The results showed that in the BSCP group, it caused significant suppression of body weight gain and suppression of white adipose tissue weight compared with the YSCP group. Moreover, it significantly decreased serum leptin levels, which correlated with visceral fat mass, and increased antidiabetic adipocytokine and adiponectin levels. Therefore, this suggests the pigmented components contained in BSCP have an antiobesity effect in obese model mice. It is suggested that this material, which can be prepared without extraction with an organic solvent and is suitable for use as a food material, could be a functional food material with a practicable antiobesity effect.